HUBUNGAN PENGASUHAN AYAH DENGAN KEMANDIRIAN ANAK USIA DINI DI DESA SURYA ADI KECAMATAN MESUJI KABUPATEN OKI - Septianingrum, Dila; Fitri, Izza; Marlina, Leny; Yuniar, Yuniar; Oktamarina, Lidia (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This study aims to determine the relationship between father's care and early childhood independence. The research method is quantitative. The correlational approach is an approach that looks for the relationship between one variable and another. The population is children aged 5-6 years. The observation that researchers use is directly to the research location in Block F Surya Adi Village. The results of observations, interviews, and the results of the father's parenting questionnaire and early childhood independence questionnaire, namely most of the parenting is neglectful parenting. From the results of the calculation of the X variable questionnaire (father's care) with the results of the calculation of variable Y (early childhood independence), the product moment correlation analysis is used to determine the relationship between the two variables, namely the relationship between variable X (father's care) with variable Y (early childhood independence). Based on the results of the study through statistical calculations conducted by researchers, it shows that parenting has a very significant relationship to early childhood independence, with a correlation of 1.03 and there is a very significant relationship between variable X and variable Y.